COVID-19 and Educational Inequality: How School Closures Affect Low- and High-Achieving Students - Elisabeth Grewenig; Philipp Lergetporer; Katharina Werner; Ludger Wößmann; Larissa Zierow (ZBW - Leibniz Information Centre for Economics, 2021)
In spring 2020, governments around the globe shut down schools to mitigate the spread of the novel coronavirus. We argue that low-achieving students may be particularly affected by the lack of educator support during school closures. We collect detailed time-use information on students before and during the school closures in a survey of 1,099 parents in Germany. We find that while students on average reduced their daily learning time of 7.4 hours by about half, the reduction was significantly larger for low-achievers (4.1 hours) than for high-achievers (3.7 hours). Low-achievers disproportionately replaced learning time with detrimental activities such as TV or computer games rather than with activities more conducive to child development. The learning gap was not compensated by parents or schools who provided less support for low-achieving students.
Keywords: I24; J62; D30; 330; educational inequality; COVID-19; low-achieving students; home schooling; distance teaching